Experience with Cadaveric Arterial Conduits as Hemodialysis Access. (July 2018) - Kenwar, Deepesh; Sharma, Ashish; Singh, Sarbpreet; Singh, Navdeep; Kapoor, Kunal
Abstract : Background: Better and more widespread dialysis availability has resulted in longer patient survival sometimes resulting in exhaustion of all possible native AV fistula sites. Synthetic AV fistula graft have been the traditional alternative in such patients but in our experience have been plagued with late AV fistula infections and outflow stenosis requiring multiple interventions. Being in a developing nation the overall costs of synthetic grafts and the management of their complications has often been prohibitively high for many patients at our center. The expanding deceased donor transplant program at our center has provided us the opportunity to explore cadaveric arterial conduits as a more economic option to salvage vascular access in such patients. Method: Retrospective analysis of hospital records on 7 patients who received cadaver derived arterial conduits as AV fistula grafts was conducted to review outcomes. Patients who were offered this option were already on long term dialysis, had no native fistula access sites remaining, were not candidates for transplantation nor for peritoneal dialysis. Cadaver derived iliac arteries were preserved in a sterile antibiotic solution and denatured with glutaraldehyde prior to implanting. Hemodialysis access was allowed once the initial inflammation had settled and surgical incision had healed. Follow up was fortnightly for the first 6 weeks and 3 monthly thereafter with additional visits whenever indicated. Results: Of the 7 (M:F 3:6) one patient was aged 29 years and the mean age for the remaining 6 was 64.85 +- 5.55 yrs. The total duration of follow up was 51.25 months (mean 5.8 +- 3.5) while the total dialysis access period was 42 months (Mean 6.0 +- 1.52). Mean conduit diameter was 8.62 mm (SD 3.19). Complications included late pseudoaneurysm formation at cannulation site (n=1), death with functioning dialysis access (n=2), steal phenomenon (n=1), inflow stenosis (n=2), outflow stenosis (n=2) and transient lymph leak (n=2). Five patients did not require further intervention. Four patients required a total of 7 interventions (4 angioplasty, 1 replacement, 1 distal revascularization, 1 pseudoaneurysm excision). Conclusions: Cadaver derived arterial conduits appear to provide one alternative to traditional synthetic grafts in patients who have exhausted native fistula options but require long term hemodialysis access and are not candidates for transplantation while being at high risk of complications such as infection of the dialysis access. The risk of deterioration of the conduit over time may be offset by the lower life expectancy in this subset of patients and ease of procuring and replacing such conduits.